α-Band oscillations in intracellular membrane potentials of dentate gyrus neurons in awake rodents - Anderson, Ross W. (Learn Mem, 2014)
The hippocampus and dentate gyrus play critical roles in processing declarative memories and spatial information. Dentate granule cells, the first relay in the trisynaptic circuit through the hippocampus, exhibit low spontaneous firing rates even during locomotion. Using intracellular recordings from dentate neurons in awake mice operating a levitated spherical treadmill, we found a transient membrane potential α-band oscillation associated with the onset of spontaneous motion, especially forward walking movements. While often subthreshold, α oscillations could regulate spike timing during locomotion and may enable dentate gyrus neurons to respond to specific cortical afferent pathways while maintaining low average firing rates.